2014
DOI: 10.4314/ajtcam.v11i3.12
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidantactivities <i>In Vitro</i> And Hepatoprotective Effects Of <i>Nelumbo Nucifera</i> Leaves <i>In Vivo</i>

Abstract: Background: Herbal medicines played a major role in the treatment of hepatic disorders, and a number of medicinal plants and their compounds were widely used for the treatment of these disorders, and oxidant stress injury was one of the mechanism of liver injury. Materials and Methods:Antioxidant activity of Nelumbo nucifera leaves (NU) extracts was assayed by the methods of scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2´-azino-bis (3-ethylbenzo-thiazoline-6-sulfonicacid) (ABTS) radical and ferric reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…It has been reported that silymarin functions as an antioxidant by scavenging oxygen free radicals and decreasing lipid peroxidation to accelerate hepatocyte regeneration with minimal adverse actions ( 35 38 ). The results of the present study were consistent with previous studies ( 39 41 ). The activities of antioxidant enzymes, including SOD, CAT, GST and GSH-Px, were decreased, while MDA production increased in the liver of rats in the TP group.…”
Section: Discussionsupporting
confidence: 94%
“…It has been reported that silymarin functions as an antioxidant by scavenging oxygen free radicals and decreasing lipid peroxidation to accelerate hepatocyte regeneration with minimal adverse actions ( 35 38 ). The results of the present study were consistent with previous studies ( 39 41 ). The activities of antioxidant enzymes, including SOD, CAT, GST and GSH-Px, were decreased, while MDA production increased in the liver of rats in the TP group.…”
Section: Discussionsupporting
confidence: 94%
“…Lotus and its leaves have certain biological activities, in particular, some studies showed that they had good antioxidant activity, and their antioxidant activity also played a protective role in cells, especially on liver cells and liver [41][42][43][44]. In addition, the lotus seed was also rich in alkaloids, which could inhibit liver injury [1].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies indicate that Silymarin exhibits strong antioxidant activity [ 36 ] and shows protective effects against hepatic toxicity induced by a wide variety of agents by inhibiting lipid peroxidation [ 30 , 37 ]. Higher total phenolic content has been known to contribute to the antioxidant activity of extracts [ 38 ], while antioxidant activity has also been linked to the hepatoprotective effect of some extracts [ 38 , 39 ]. These findings corroborate with our results on the ability of SLM to exert a hepatoprotective activity.…”
Section: Discussionmentioning
confidence: 99%